The relationship between the firms characteristics and returns in the property sector of Bursa Malaysia Main Board From 2003 – 2007 / Antony Puro - Puro, Antony (2008)
This study is conducted to determine if there is any significant correlation between the firms characteristics (Beta, Size and Leverage) and returns, Dividend Yield ( DIY ) in the property sector of Bursa Malaysia for the period 2003 - 2007. This is the period after the Malaysian economy has recovered from the 1997 - 1998 Asian economic crisis. Financial data from 35 active Malaysian Property shares companies listed on the Property Sector of Bursa Malaysia Main Board were utilized. The findings have revealed that there is significant correlations between the firms characteristic, Beta and Size(independent variables) and returns (dependent variable ) whereas Leverage has no significant correlation.